Supervision of Goods Resulting from Trade With Non-Trade Online Deposit Business Activities (Permenkeu No. 96 of 2023) - Ervina, Ervina; Pakpahan, Kartina; Pakpahan, Elvira Fitriyani (International Journal of Business, Law, and Education, 2024)
This research is motivated by the fact that online deposit business activities have recently become more widespread in line with advances in information and telecommunications technology. These activities are generally regulated through Minister of Finance Regulation Number 96 of 2023 concerning Customs, Excise and Tax Provisions for the Import and Export of Consigned Goods. Minister of Finance Regulation Number 96 is actually a replacement for the Minister of Finance Regulation Number 199/ PMK.010/ 2019 concerning Customs, Excise and Tax Provisions for Imported Consigned Goods previously. Minister of Finance Regulation Number 96 of 2023 itself, is an important regulation relating to services or online deposit business. The legal research method used in this research is normative juridical research which is research carried out or aimed only at written regulations with the nature of descriptive analysis research which is a method that functions to describe or provide an overview of the object being studied. The data source used is secondary data with quantitative data analysis. The results of this research are the implementation of Minister of Finance Regulation No. 96 of 2023 concerning Customs, Excise and Tax Provisions for the Import and Export of Shipped Goods regarding online deposit business activities is more aimed at avoiding the legal mode in the form of illegal import practices. The impact of the policy of Minister of Finance Regulation Number 96 of 2023 means that Jastip UMKM players in the e-commerce sector must adapt to technological advances, including the form of sales and purchase agreements in jastip, as well as causing consumers to have to consider the value of the goods they order because it affects the tax that must be paid.